2012
DOI: 10.1038/labinvest.2011.132
|View full text |Cite
|
Sign up to set email alerts
|

Vision preservation during retinal inflammation by anthocyanin-rich bilberry extract: cellular and molecular mechanism

Abstract: Anthocyanin-rich bilberry extract, a plant-derived antioxidant, has been utilized as a popular supplement for ocular health worldwide. However, it is unclear whether this extract has any biological effect on visual function, and the mechanism for such an effect is completely unknown. In this study, we generated a mouse model of endotoxin-induced uveitis (EIU) that shows retinal inflammation, as well as uveitis, by injecting lipopolysaccharide. We pretreated the mice with anthocyanin-rich bilberry extract and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 32 publications
5
67
1
1
Order By: Relevance
“…Most of the berries have high anthocyanins content. Oral administration of bilberry extract (contained about 39% anthocyanins) to six weeks old C57BL/6 mice has been shown to prevent impairment of photoreceptor cell function during retinal inflammation [91]. In another study, 132 patients with normal tension glaucoma were supplemented with two anthocyanins capsules (60.0 mg anthocyanin in each capsule) from bilberry daily and have improved visual function, based on the Humphrey visual field test and minimal angle of resolution best-corrected visual acuity assessment [90].…”
Section: Nutraceutical and Pharmaceutical Effects Of Anthocyaninsmentioning
confidence: 99%
“…Most of the berries have high anthocyanins content. Oral administration of bilberry extract (contained about 39% anthocyanins) to six weeks old C57BL/6 mice has been shown to prevent impairment of photoreceptor cell function during retinal inflammation [91]. In another study, 132 patients with normal tension glaucoma were supplemented with two anthocyanins capsules (60.0 mg anthocyanin in each capsule) from bilberry daily and have improved visual function, based on the Humphrey visual field test and minimal angle of resolution best-corrected visual acuity assessment [90].…”
Section: Nutraceutical and Pharmaceutical Effects Of Anthocyaninsmentioning
confidence: 99%
“…Few recent studies have shown the efficacy of anthocyanins in treating inflammatory and neurogenerative diseases (Jeong et al, 2013). Recently, (Miyake et al, 2012) retinal inflammation affecting vision was treated with anthocyanins from bilberry extracts. Purified anthocyanins in clinical trials were demonstrated to improve ocular health (Lee et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenols, including flavonoids, and especially anthocyanins, are the main components of bilberries [19]. The anthocyanin-rich BE has been used as a pharmaceutical product and popular treatment for vision health problems worldwide [20,21].…”
Section: Discussionmentioning
confidence: 99%